2007
DOI: 10.1111/j.1469-8137.2007.02138.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the cyclic lipopeptide massetolide A in biological control of Phytophthora infestans and in colonization of tomato plants by Pseudomonas fluorescens

Abstract: Summary• Pseudomonas strains have shown promising results in biological control of late blight caused by Phytophthora infestans . However, the mechanism(s) and metabolites involved are in many cases poorly understood. Here, the role of the cyclic lipopeptide massetolide A of Pseudomonas fluorescens SS101 in biocontrol of tomato late blight was examined.• Pseudomonas fluorescens SS101 was effective in preventing infection of tomato ( Lycopersicon esculentum ) leaves by P. infestans and significantly reduced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
179
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(195 citation statements)
references
References 49 publications
5
179
0
1
Order By: Relevance
“…Certain antimicrobial compounds produced by rhizobacteria possess the capacity to limit plant disease development, both directly by limiting growth of the pathogen and indirectly via the induction of plant defense responses (13,31,37). Recent studies by Tran et al (36) indicated that massetolide A induces resistance in tomato plants against Phytophthora infestans. Work by Ongena et al (27) suggested that fengycins, CLPs produced by B. subtilis, could be involved in eliciting induced resistance, whereas the structurally different CLP mycosubtilin most likely does not have resistance-inducing activities (17).…”
Section: Discussionmentioning
confidence: 99%
“…Certain antimicrobial compounds produced by rhizobacteria possess the capacity to limit plant disease development, both directly by limiting growth of the pathogen and indirectly via the induction of plant defense responses (13,31,37). Recent studies by Tran et al (36) indicated that massetolide A induces resistance in tomato plants against Phytophthora infestans. Work by Ongena et al (27) suggested that fengycins, CLPs produced by B. subtilis, could be involved in eliciting induced resistance, whereas the structurally different CLP mycosubtilin most likely does not have resistance-inducing activities (17).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transgenic Arabidopsis NahG plants that are unable to accumulate SA due to ectopic expression of the bacterial salicylate hydroxylase gene nahG, showed a similar level of induced disease resistance upon colonization of the roots by WCS417r as did wildtype plants, indicating that WCS417r-ISR functions independently of SA (Pieterse et al, 1996). Since then, many examples of SA-independent ISR have been demonstrated in Arabidopsis (Ahn et al, 2007;Iavicoli et al, 2003;Ryu et al, 2003;Segarra et al, 2009;Stein et al, 2008;Van Wees et al, 1997) and other plant species, such as tobacco (Press et al, 1997;Zhang et al, 2002), cucumber (Press et al, 1997), tomato (Hase et al, 2008;Tran et al, 2007;Yan et al, 2002), and rice (De Vleesschauwer et al, 2008). Hence, the ability to activate an SA-independent pathway controlling systemic disease resistance seems to be common for beneficial microorganisms and occurs in a broad range of plant species against different types of attackers.…”
Section: Sa-independent Signalingmentioning
confidence: 99%
“…ISR can also take place following exposure of the plant to compounds produced by plant-beneficial bacteria, e.g. the volatile 2,3-butanediol (Ryu et al 2004), the siderophore pyoverdine (Maurhofer et al 1994), DAPG (Iavicoli et al 2003), and cyclic lipopeptide surfactants (Ongena et al 2007;Tran et al 2007). …”
Section: Direct Positive Effects Of Rhizosphere Microorganisms On Thementioning
confidence: 99%